A review of recent studies on the pathogenesis of Systemic Sclerosis: focus on fibrosis pathways - Jimenez, Sergio A.; Mendoza, Fabian A.; Piera-Velazquez, Sonsoles (Frontiers in Immunology, 2025)
Systemic Sclerosis (SSc) is a systemic autoimmune disease of unknown etiology characterized by the development of frequently progressive cutaneous and internal organ fibrosis accompanied by severe vascular alterations. The pathogenesis of SSc is highly complex and, despite extensive investigation, has not been fully elucidated. Numerous studies have suggested that unknown etiologic factors cause multiple alterations in genetically receptive hosts, leading to SSc development and progression. These events may be functionally and pathologically interconnected and include: 1) Structural and functional microvascular and endothelial cell abnormalities; 2) Severe oxidative stress and high reactive oxygen species (3); Frequently progressive cutaneous and visceral fibrosis; 4) Transdifferentiation of various cell types into activated myofibroblasts, the cells ultimately responsible for the fibrotic process; 5) Establishment of a chronic inflammatory process in various affected tissues; 6) Release of cytokines, chemokines, and growth factors from the inflammatory cells; 7) Abnormalities in humoral and cellular immunity with the production of specific autoantibodies; and 8) Epigenetic alterations including changes in multiple non-coding RNAs. These events manifest with different levels of intensity in the affected organs and display remarkable individual variability, resulting in a wide heterogeneity in the extent and severity of clinical manifestations. Here, we will review some of the recent studies related to SSc pathogenesis.